Theoretical and numerical investigation of Carreau–Yasuda fluid flow subject to Soret and Dufour effects. (April 2020) - Ijaz Khan, M.; Hayat, T.; Afzal, Sidra; Imran Khan, M.; Alsaedi, A.
Highlights: Here flow of Carreau–Yasuda fluid is addressed over a porous surface. Energy equation is modeled subject to Soret and Dofour effects. Mixed convection is considered. Numerical results are calculated via bvp4c. Abstract: Background: Newtonian fluids can be categorized by a single coefficient of viscosity for specific temperature. This viscosity will change with temperature; it doesn't change with strain rate. Just a small group of liquids show such steady consistency. A fluid whose viscosity changes subject to relative flow velocity is called non-Newtonian liquids. Here we have summarized a result for the flow of Carreau–Yasuda fluid over a porous stretchable surface. Mixed convection is considered. Modeling of energy expression is performed subject to Soret and Dufour effects. Method: The nonlinear PDE's are changed to ODE's through suitable transformations and then solved for numerical solutions via Built-in shooting method (bvp4c). Results: Variation of important variables is studied on the concentration, temperature and velocity fields. Tabular representation for study of skin friction and heat transfer rate is presented for important variables. Our results show that velocity decreases versus higher estimations of Weissenberg number, porosity parameter, buoyancy ratio and mixed convection parameter. Temperature decays via Weissenberg number and porosity parameter. Increase in concentration is noticed through higher Soret number and porosity parameter. Skin friction and heat transfer rate (Nusselt number) boosts versus larger porosity parameter and Prandtl number respectively while it decays against Weissenberg number and Dufour and Eckert number.